The combination of Benzaldehyde and Nickel‐catalyzed photoredox C(sp3)-H alkylation/arylation - Zhang, Lumin; Si, Xiaojia; Yang, Yangyang; Zimmer, Marc; Witzel, Sina; Sekine, Kohei; Rudolph, Matthias; Hashmi, A. Stephen K. (Angewandte Chemie. International edition, 2019)
Herein we report a highly selective photoredox C(sp3)−H alkylation/arylation of ethers through the combination of a photo‐organocatalyst (benzaldehyde) and a transition‐metal catalyst (nickel). This method provides a simple and general strategy for the C(sp3)−H alkylation/arylation of ethers. A selective late‐stage modification of (−)‐ambroxide has also been conducted to demonstrate the applicability of the method.